PENGARUH KEPEMIMPINAN, DISIPLIN KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI POLITEKNIK ILMU PELAYARAN SEMARANG (Students' Journal of Economic and Management, 2013)
This research is a study that tested the effect of leadership, labor discipline and organizational culture on employee performance. This study aims to examine and analyze the effect of leadership, labor discipline, and organizational culture on employee performance and simultaneous partial.In this study, researchers used a sample of 100 respondents employee Politeknik Ilmu Pelayaran Semarang, the data obtained from the questionnaire. Then tested with questionnaire data validity and reliability, having obtained a valid result, then studies using multiple linear regression to describe the relationship between the variables.The result is the result of the hypothesis that demonstrate leadership and significant positive effect on employee performance, while labor discipline positive and significant effect on employee performance and organizational culture have a positive and significant effect on employee performance.Keywords: Leadership, Labor Discipline , Organizational Culture and Employee Performance